2009
DOI: 10.1021/om9006032
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Sodium Diisopropylamide (NADA): Formation of a New Transition Metalate via Silyl Migration Chemistry, [(η5-Me3SiC5H4)Fe(CO)(PPh3)]Na+(SiFpPNa), and Resulting Thermal Rearrangements of the Complexes SiFpP−CH2SiMe2R (R = H, SiMe3) to SiFpP−SiMe2CH2R

Abstract: A new transition metalate system, [(η 5 -Me 3 SiC 5 H 4 )Fe(CO)(PPh 3 )] -M þ (SiFpPM; M = Li, Na), was synthesized via treatment of (η 5 -C 5 H 5 )Fe(CO)(PPh 3 )SiMe 3 with sodium and lithium diisopropylamides (MN(iPr 2 ); NADA and LDA, respectively). The utility of NADA was far superior to that of LDA, with shorter reaction times, lower reagent concentrations, and higher yields. Infrared spectroscopic analysis of the new ferrates indicated that their stability and utility were dependent upon the tight ion pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Attempts to synthesize 1 via homogeneous reactions in ethereal solvents were unsuccessful resulting in a mixture of products among which we could identify FpSn t Bu 2 Cl, a previously characterized complex [8]. The utility of such heterogeneous reactions of the Fp salt [9], or use of non-coordinating solvents for soluble variants of the Fp anion [10], to yield desired products rather than side-products involving (1) -NaCl secondary reactions has been reported previously. Clearly the ionpairing aspect of the salt is important.…”
Section: Synthesis and Structures Of 1 Andmentioning
confidence: 77%
“…Attempts to synthesize 1 via homogeneous reactions in ethereal solvents were unsuccessful resulting in a mixture of products among which we could identify FpSn t Bu 2 Cl, a previously characterized complex [8]. The utility of such heterogeneous reactions of the Fp salt [9], or use of non-coordinating solvents for soluble variants of the Fp anion [10], to yield desired products rather than side-products involving (1) -NaCl secondary reactions has been reported previously. Clearly the ionpairing aspect of the salt is important.…”
Section: Synthesis and Structures Of 1 Andmentioning
confidence: 77%
“…Metalation of substituted arenes by NaDA must have been examined and possibly even reported, but our failure to find a literature example underscores a glaring omission (eq 2 ). In this paper, we describe NaDA-mediated arene sodiation from a synthetic organic and mechanistic perspective …”
Section: Introductionmentioning
confidence: 99%
“…Other uses of NaDA (Scheme 11) include the metalation of diphenylmethane, 7 a cyclopentadienyl iron complex, 39 fluoroform, 40 and a few ketones (vide infra). The dates…”
Section: C-h Metalationmentioning
confidence: 99%
“…31 The practicality of the protocol is illustrated by isomerization of neat 37b with catalytic NaDA. Rate studies showed a curious alternating preference for tri-, di-, and tri-solvated dimers with increasing substituent size from Me 3 Si to t-BuMe 2 Si to i-Pr 3 Si (39)(40)(41). Substitution at the 3-position (42 and 43) affords dienes (Scheme 18), whereas an alkyl moiety at the one position simply fails to isomerize.…”
Section: Allyl Ether Isomerizationsmentioning
confidence: 99%